Pengaruh Ketidakpuasan Konsumen, Kebutuhan Mencari Variasi Dan Word Of Mouth Terhadap Keputusan Perpindahan Merek Pada Lipstik Merek Implora Ke Wardah (Study Kasus Pada Mahasiswi FEB UNISMA 2017) - Fidiah Anggraeni; Nurhajati Nurhajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to examine the effect of consumer dissatisfactio, the need of variety seeking and word of mouth on the decision to switch brands on the Implora to Wardah lipstick brand. The population in thi study were FEB UNISMA 2017 students. The sample selection is female students who have used Implora and Wardah Lipsticks. In this study using the technique purposive sampling. The number of sample used were 70 FEB UNISMA 2017 students. The analytical technique used in this research is multiple liniear regression analysis using quantitative methods.The results of this study indicate that (1) Consumer dissatisfaction, need to variety seeking and word of mouth simultaneously have a positive and significant effect on brand switching decisions (2) Consumer dissatisfaction partially has a positive and significant effect on brand switching decisions (3) the need to variety seeking partially does not have a significant effect on brand switching decisions (4) word of mouth partially has a positivie and significant affect on brand switching decisions. Keyword : Consumer dissatisfaction, need to variety seeking, word of mouth and brand swutching decision.